Nintedanib promotes antitumour immunity and shows antitumour activity in combination with PD-1 blockade in mice: potential role of cancer-associated fibroblasts - Kato, Ryoji; Haratani, Koji; Hayashi, Hidetoshi; Sakai, Kazuko; Sakai, Hitomi; Kawakami, Hisato; Tanaka, Kaoru; Takeda, Masayuki; Yonesaka, Kimio; Nishio, Kazuto; Nakagawa, Kazuhiko (British journal of cancer, 2021)
Background Cancer-associated fibroblasts (CAFs) in the tumour microenvironment (TME) suppress antitumour immunity, and the tyrosine kinase inhibitor nintedanib has antifibrotic effects. Methods We performed a preclinical study to evaluate whether nintedanib might enhance antitumour immunity by targeting CAFs and thereby improve the response to immune checkpoint blockade (ICB). Results Whereas nintedanib did not suppress the growth of B16-F10 melanoma cells in vitro, it prolonged survival in a syngeneic mouse model of tumour formation by these cells, suggestive of an effect on the TME without direct cytotoxicity. Gene expression profiling indeed showed that nintedanib influenced antitumour immunity and fibrosis. Tumoural infiltration of CD8 + T cells and granzyme B production were increased by nintedanib, and its antitumour activity was attenuated by antibody-mediated depletion of these cells, indicating that nintedanib suppressed tumour growth in a CD8 + T cell-dependent manner. Moreover, nintedanib inhibited the proliferation and activation of fibroblasts. Finally, the combination of nintedanib with ICB showed enhanced antitumour efficacy in B16-F10 tumour-bearing mice. Conclusions Our results suggest that nintedanib targeted CAFs and thereby attenuated the immunosuppressive nature of the TME and promoted the intratumoural accumulation and activation of CD8 + T cells, with these effects contributing to enhanced antitumour activity in combination with ICB.